The classification of knowledge in Islam by Imam Al- Ghazali and Al- Farabi - Ashimi, Tijani Ahmad (Asian Scholars Network, 2022)
Abstract It is undeniable fact that history is the record of past events and civilization is an advance development in the society marked by rapid progress in economy, politics, science, knowledge and Information technology. Down the centuries, Islam as a religion of comprehensive way of life. It has paid a huge attention to knowledge, it invites people to seek it at all costs; it also urges them to think and contemplate in order to reach the true meaning of ontological reality. If that indicates something, it proves that Islam is totally against ignorance and illiteracy. Based on this fact Islamic civilization during its golden era has witnessed some splendid Muslim scholars who shoulder the message of Islam and whose contributions to the field of different knowledge can not be underestimated. For instance, Imam Al- Ghazali(Hujjah Al-Islam) and Al- Farabi are renouwned Muslim scholars of all time. They both contributed immensely to the field of social sciences , humanities and mysticism. Their contributions to these field have become great references to contemporary Muslim scholars in their academic researches. Thus, the main objective of this paper is to investigate the classification of knowledge by Imam Al- Ghazali and Al- Farabi respectively. Yet, in order to achive our objective the comparative approach is applied followed by brief conclusion and some recommendations Keywords: Imam Al- Ghazali, Al- Farabi, Classification of knowledge,, Islam, Qur’an, Sunnah.